Apoptotic response after in vivo infection of turbot (Scophtalmus maximus) with viral haemorragic septicaemia virus (VHSV), infectious pancreatic necrosis virus (IPNV) and nodavirus - Novoa, Beatriz; Montes, Ariana; Figueras Huerta, Antonio (2010)
8th International Symposium on Viruses of Lower Vertebrates, Santiago de Compostela (España), 26-29 abril 2010 No